Reflexive pronominal forms in children's Spanish - Esquivel Villafana, Jorge (1999)
In the syntactic analysis of the Spanish sentence, the treatment of so-called reflexive verbs deserves special consideration, that is, those that can be accompanied by reflexive pronominal forms (me, te, nos, os, se).